IMPLEMENTATION OF RELIGIOUS MODERATION IN GERAKAN PEMUDA ANSOR CIAMIS DISTRICT AS AN EFFORT TO PREVENT RADICALISM - Yoga Nugraha Marlyono; Dadan Wildan; Yadi Ruyadi (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
Indonesian people live in an environment full of diversity, both ethnic, linguistic, cultural and religious, spread from Sabang to Merauke. This diversity is shaded by the ideology of Pancasila and the motto Bhinneka Tunggal Ika which must be a guide for the community. However, currently threats that can divide the Republic of Indonesia amidst this diversity are still emerging, one of which is radicalism. Religious moderation is one method that is currently being advocated by many organizations and institutions to prevent the growth and development of radicalism. One of the organizations that develops religious moderation is the Ansor Gerakan Pemuda Ansor in Ciamis district as an effort to prevent radicalism. This research uses a qualitative approach with a case study method. Data collection techniques in this research are interviews, observation and documentation studies. Interviews were conducted with NU administrators, GP Ansor administrators, and GP Ansor cadres. Data analysis techniques include data reduction, data presentation, and conclusions and verification. The research results show that the implementation of religious moderation carried out by the Ciamis Regency Gerakan Pemuda Ansor  Organization has a culture and programs that are able to distance its cadres from radicalism. Some of the programs from this organization include cadre formation for prospective cadres to form loyalty to the organization, strengthen understanding of statehood and tolerance. Then uphold the principles of the Unitary Republic of Indonesia's fixed price, a culture of democratic and inclusive discussion, studies that do not only focus on religious issues, and maintaining good relations across organizations and across religions. This good program is also wrapped in a solid organizational culture for mutual development which implicitly is the realization of Sundanese philosophical values, namely silih asih, silih asih, and sililh asuh.